Preliminary Study on Preparation Method of Gas Simulation Source Based on Silicon Aerogel - Juhan LAI; Wen XIA; Shunhe YAO; Lijun XU; Yuntao LIU; Lingze MENG; Junbo ZHANG; Yuanqiao LI (Journal of Isotopes)
In order to prepare a simulation source that can replace 13N(T1/2=9.97 min) gas for direct calibration of 13N monitor，this paper adopts two-step wet gel preparation technology and CO2 supercritical drying technology to carry out research on the preparation process of silicon-based aerogel. TEOS is used as raw material to prepare precursor solution. After the precursor system was prepared，add acetone 45 times of the precursor raw material to dilute it，and the gel was gelled at pH=8. After supercritical drying,the preparation of the aerogel matrix meeting the requirement is finished. Based on this process，a 22Na (T1/2=2.60 a) gas simulation source was developed for calibration of a 13N monitor with a density of 4.6 mg/cm3 (4 times the air density), the intra-batch uniformity was 5%，and the inter-batch uniformity was 8%. A gas simulation source was used to calibrate the efficiency of a 13N monitor prototype，and there was a 25% relative deviation from the simulation results.